Algorithmic vulnerabilities and the datalogical: Early motherhood and tracking-as-care regimes. (April 2019) - Thornham, Helen
This article draws on work from a 6-month project with 12 young mothers in which we mapped and tracked ourselves and our infants. The project employed a range of methods including digital ethnographies, walk-along methods, hacking and playful experimentations. We explored, broke and tested a range of wearables and phone-based tracking apps, meeting regularly to discuss and compare our experiences and interrogate the sociotechnical systems of postnatal healthcare alongside the particular politics of certain apps and their connective affordances. In this article, I use the project as a springboard to explore what I call algorithmic vulnerabilities: the ways that the contemporary datalogical anthropocene is exposing and positioning subjects in ways that not only rarely match their own lived senses of identity but are also increasingly difficult to interrupt or disrupt. While this is not necessarily a new phenomenon (see Clough et al., 2015; Hayles, 2017), I argue that the particular algorithmic vulnerabilities within this context, which are forged in part through the ideological enmeshing of the long-running atomization of maternal and infant bodies within the healthcare systems (Crowe, 1987; Shaw, 2012; Wajcman, 1991) and the new and emergent tracking apps (Greenfield, 2016; Lupton, 2016; O'Riordan, 2017) create momentary stabilizations of sociotechnical systems in which maternal subjectivity and female embodiment become algorithmically vulnerable in affective and profound ways. These stabilizations become increasingly and problematically normative, partly because they feed and perpetuate a wider 'taken-for granted' sensibility of gendered neoliberalism (Gill, 2017: 609) which, as I argue, is coming to encapsulate the contemporary datalogical anthropocene. Secondly, the sociotechnical politics of the apps and the healthcare systems are revealed as co-dependent, raising a number of questions about long-term algorithmic vulnerabilities and normativities which predate the contemporary datalogical 'turn' and impact both practices and methods.